Low-temperature silver-coated copper slurry for heterojunction battery as well as preparation method and application of low-temperature silver-coated copper slurry
By developing low-silver-containing low-temperature silver-clad copper paste suitable for nickel screen printing, the resin components are optimized to improve printing performance, and the problems of high metallization cost of HJT batteries and poor printing performance of silver-clad copper paste are solved, achieving cost reduction and efficiency improvement and efficient battery conversion efficiency.
Patent Information
- Application Number
- CN202411871746.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-05-02
AI Technical Summary
The metallization cost of HJT batteries is relatively high, especially the cost of low-temperature silver paste, which affects the commercialization process of the battery. At the same time, silver-clad copper paste has poor printing performance during nickel screen printing, making it difficult to adapt to nickel screens with narrow line widths.
A low-temperature silver-clad copper paste with low silver content is developed, suitable for nickel screen printing, and improves over-inking properties and linear fluency by optimizing resin components, including epoxy resin with an epoxy equivalent of 200-260 and rubber toughened epoxy resin with a weight average molecular weight of 10000-20000.
On the basis of greatly reducing single-piece silver consumption, it improves light utilization and cell conversion efficiency, reduces the entire life cycle cost of photovoltaics, and is suitable for nickel screen printing with high requirements for slurry.
Smart Images

Figure CN119920522A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of HJT batteries, and in particular to a low-temperature silver-coated copper slurry for heterojunction batteries, a preparation method and an application thereof, wherein the slurry is suitable for nickel screen printing. Background Art
[0002] HJT cells, or heterojunction cells, are based on the use of amorphous silicon deposition technology to form a heterojunction passivation layer on N-type silicon wafers. This design significantly improves the open circuit voltage and conversion efficiency of the cell. In addition, heterojunction cells combine the dual advantages of crystalline silicon solar cells and thin-film technology, with a series of advantages such as high conversion rate, simple manufacturing process, thin silicon wafer application, low temperature coefficient and double-sided power generation. It is known as the next generation of high-efficiency battery technology with the greatest industrial potential. At present, the mass production efficiency of heterojunction cells is about 24%, with huge room for efficiency improvement and excellent development prospects.
[0003] At present, the relatively high cost of HJT metallization has become the main factor restricting the large-scale commercialization of HJT batteries. The proportion of HJT non-silicon costs is higher than that of PERC, mainly because the non-silicon costs of HJT low-temperature silver paste, target materials, equipment, etc. are relatively high. For low-temperature silver paste, in addition to reducing unit consumption through fine-line printing and 0BB technology, the metal route of base metals such as silver-clad copper is also actively promoting the industrialization verification of technology.
[0004] The principle of silver-coated copper paste is simple, the cost-reduction effect is obvious, and the impact on conversion efficiency is small, and the technical prospects are good. In the screen printing process, the silver-coated copper paste is relatively poor in printing performance compared to pure silver paste due to the difference in powder particle size, and the printing performance is mostly positively correlated with the silver content. Therefore, when adapting to narrow line width screens and new printing processes such as nickel screens and steel screens, it is particularly necessary to formulate low-silver-content silver-coated copper paste to optimize printing. Summary of the invention
[0005] The present invention provides a low-temperature silver-coated copper slurry for heterojunction batteries and a preparation method and application thereof. By developing a new low-silver-containing low-temperature silver-coated copper slurry suitable for nickel screen printing and matching the new nickel screen process, the grid line width is greatly reduced after printing, and the minimum can be 18 microns. The grid line height remains unchanged. On the basis of reducing unit consumption, high conversion efficiency is achieved, while cost reduction and efficiency improvement are achieved, and the photovoltaic life cycle cost is diluted. The low-temperature silver-coated copper slurry for heterojunction batteries provided by the present invention is particularly suitable for nickel screens with high slurry requirements. Of course, in addition to this, it can also be applied to screen printing, narrow line width screens, and steel screens with relatively low slurry requirements.
[0006] The technical solution of the present invention is as follows:
[0007] The first aspect of the present invention provides a low-temperature silver-coated copper paste for heterojunction batteries, which can be suitable for nickel screen printing and includes the following components by mass ratio: 10%-70% of spherical silver-coated copper powder, 15-80% of submicron silver powder, 0.5-5% of nano silver powder, 1-6% of resin, 0.2-4% of auxiliary agent, and 0.5-3% of solvent, wherein the resin includes an epoxy resin with an epoxy equivalent of 200-260 and a rubber-toughened epoxy resin with a weight-average molecular weight of 10,000-20,000.
[0008] Further preferably, in terms of mass ratio, the spherical silver-coated copper powder is 45%-70%, and the silver powder is 18-45%.
[0009] In the slurry formula of the present invention, the epoxy resin with an epoxy equivalent of 200-260 is a low molecular weight, low polarity resin, which is used to provide ink permeability and ensure the narrow line width printing of the nickel mesh; the high molecular weight resin (i.e., the rubber toughened epoxy resin with a weight average molecular weight of 10000-20000) is used as a thixotropic agent to ensure the printing line type and high aspect ratio. Such a formula design makes the slurry of the present invention suitable for nickel mesh printing with high slurry requirements. By adopting the above technical solution and matching the nickel mesh narrow line width printing, the printing line width can be as low as 18 microns, which can increase the light utilization rate and improve the conversion efficiency of the battery cell on the basis of greatly reducing the silver consumption of a single piece, thereby achieving the purpose of reducing costs and increasing efficiency.
[0010] Preferably, the mass ratio of the epoxy resin with an epoxy equivalent of 200-260 to the rubber toughened epoxy resin with a weight average molecular weight of 10000-20000 is 10:90-90:10. More preferably, the mass ratio of the rubber toughened epoxy resin with a weight average molecular weight of 10000-20000 in the resin is not more than 50%.
[0011] Preferably, the rubber toughened epoxy resin is an epoxy resin derivative, selected from functionalized liquid rubber toughened epoxy, composite β-cyclodextrin / terminated carboxyl liquid nitrile rubber co-toughened epoxy resin, core-shell structure rubber toughened epoxy resin, or a combination thereof.
[0012] In some embodiments, the specific surface area of the spherical silver-coated copper powder is 0.1-0.6 m 2 / g, D50 is 2.5-6 microns, and the tap density is 4.5-5.5g / m 3 The spherical silver-coated copper powder comprises one powder or a combination of multiple powders, wherein the combination of multiple powders is a combination of the above-mentioned different specific surface areas, D50 and tap density to achieve an optimal packing density.
[0013] Preferably, the submicron silver powder includes one or a combination of submicron ball powder and submicron flake powder.
[0014] Preferably, in the submicron silver powder, the particle size distribution of the submicron ball powder is D10≤0.2μm, D50≤0.6μm, D100≤1.5μm, and the tap density is 4.0-5.1g / cm 3 , specific surface area 0.7~1.3m 2 / g; the particle size distribution of the submicron flake powder is D10≤1.2μm, D50≤5μm, D100≤8μm, and the tap density is 5.1~6.2g / cm 3 , specific surface area 0.5~0.6m 2 / g.
[0015] Preferably, the average particle size of the nano silver powder is less than 0.1 μm, and the specific surface area is 2 to 5.5 m 2 / g.
[0016] The present invention uses a combination of conductive powders with different particle sizes to obtain an optimal packing density.
[0017] Preferably, the resin comprises a mixture of the epoxy resin with an epoxy equivalent of 200-260, the rubber toughened epoxy resin with a weight average molecular weight of 10000-20000, and a curing agent.
[0018] In addition, the resin may also include one or more of other epoxy resins, acrylic resins, polyurethane resins and modified derivatives thereof. The other epoxy resins refer to other epoxy resins other than the two epoxy resins mentioned above, such as glycidyl ether epoxy resins.
[0019] The curing agent is preferably one or more of amine compounds, imidazole compounds, acid anhydride compounds, isocyanate compounds, and thiol compounds; or, the curing agent is a latent curing agent. Preferably, the amine compound is one or more of dicyandiamide, boron trifluoride ethylamine complex, and boron trichloride ethylamine complex.
[0020] Preferably, the epoxy resin with an epoxy equivalent of 200-260 is one or more of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol F epoxy resin, acrylic modified epoxy resin, silicone modified epoxy resin, and polyurethane modified epoxy resin.
[0021] Preferably, the auxiliary agent includes a thixotropic agent, a leveling agent, a dispersant, a coupling agent, and an antioxidant. Among them, the thixotropic agent is preferably one or more of fumed silica, organic bentonite, hydrogenated castor oil, polyamide wax, and oleic acid amide. The leveling agent is preferably one or more of acrylic acid, modified polysiloxanes, and fluorocarbon compounds. The dispersant is preferably one or more of sulfonates, ammonium salts, carboxylates, polyesters, and polyurethanes. The coupling agent is preferably one or more of aminosilane coupling agents, epoxy-terminated silane coupling agents, titanate coupling agents, and aluminate coupling agents. The antioxidant is preferably one or more of metal ion chelators, citric acid, EDTA, and phosphoric acid derivatives.
[0022] Preferably, the solvent is one or more of diethylene glycol butyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether acetate, ethyl acetate, butyl acetate, naphtha, propylene glycol methyl ether acetate, dimethyl succinate, dimethyl glutarate, dimethyl adipate, tributyl citrate, dibutyl phthalate, butyl benzyl phthalate, butyl stearate, oleic acid, butyl oleate, terpineol, and tributyl phosphate.
[0023] A second aspect of the present invention provides a method for preparing the above-mentioned low-temperature silver-coated copper slurry for heterojunction batteries, comprising the following steps:
[0024] First, pour the liquid components such as resin, additives, solvents into the reaction kettle and stir to mix;
[0025] Then, the submicron silver powder, nano silver powder, and spherical silver-coated copper powder are added in sequence, and stirred to obtain a uniform slurry;
[0026] Then, the three-roll mill is used for grinding, and the grinding gap is adjusted from large to small to 120μm to 20μm;
[0027] Finally, the conductive silver paste is filtered through a sieve to obtain a uniformly dispersed conductive silver paste with a viscosity of 100 to 200 Pa.s.
[0028] A third aspect of the present invention provides a use of the above-mentioned low-temperature silver-coated copper paste for heterojunction batteries in preparing heterojunction batteries using nickel screen printing.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] First, the present invention provides a low-temperature slurry for manufacturing heterojunction batteries. The slurry is a silver-coated copper slurry with a low silver content and can be applied to nickel screen printing which has high requirements on the slurry.
[0031] The present invention makes a special setting for the type of resin in the slurry formula, so that the resin component includes two epoxy resins, one of which is an epoxy resin with an epoxy equivalent of 200-260, and the other is a rubber toughened epoxy resin with a weight average molecular weight of 10000-20000, wherein the epoxy resin with an epoxy equivalent of 200-260 is a low molecular weight and low polarity resin, which can improve the ink passing property of narrow line width nickel screen printing, improve the smoothness of the line type after printing, and improve the problem of printed flower pieces; and the rubber toughened epoxy resin with a weight average molecular weight of 10000-20000 is introduced into the system as a resin participating in the subsequent curing reaction of printing, so as to provide toughness and elasticity, ensure the line height, and provide a high grid line aspect ratio.
[0032] Second, the two epoxy resins used in the present invention are both raw materials that are easily available in existing materials and do not require special and complicated preparation processes.
[0033] Third, the low-silver silver-containing copper-clad paste of the present invention has a good matching effect with nickel screen printing, and can achieve the goal of not reducing efficiency while reducing the unit consumption of heterojunction batteries, thereby achieving cost reduction and efficiency improvement.
[0034] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a 3D result diagram of the slurry nickel screen printing of Comparative Example 1 of the present invention;
[0036] Figure 2 This is a 3D result diagram after nickel screen printing of the slurry of Example 1 of the present invention;
[0037] Figure 3 This is a 3D result diagram after nickel screen printing of the slurry of Example 2 of the present invention;
[0038] Figure 4 This is a 3D result diagram after nickel screen printing of the slurry of Example 3 of the present invention;
[0039] Figure 5 This is a 3D result diagram of the slurry after nickel screen printing of Example 4 of the present invention;
[0040] Figure 6 This is a 3D result diagram after nickel screen printing of the slurry of Example 5 of the present invention;
[0041] Figure 7 This is a 3D result diagram of the slurry after nickel screen printing of Example 6 of the present invention;
[0042] Figure 8 This is a 3D result diagram of the slurry after nickel screen printing of Example 7 of the present invention;
[0043] Fig. 9This is a 3D result diagram of the slurry after nickel screen printing of Example 8 of the present invention. DETAILED DESCRIPTION
[0044] In the solar cell process, screen printing has become the dominant method for cell metallization due to its advantages such as fast time, easy industrialization, and good stability. However, the conductive paste combined with screen printing usually has disadvantages such as unevenness and widened lines due to its own structure containing mesh knots. The nickel mesh is fully open and has no mesh knots, which is more advantageous than the screen. In addition, the nickel mesh opening is basically 12 on the front side, and the line width is extremely narrow. However, the inventors found that the silver-coated copper paste is printed on the nickel screen, and the ink flow is poor. After printing, the grid lines are ups and downs, and the line type is not smooth. In addition, when the nickel mesh is printed with a conventional slurry that matches the screen, the dense grid is prone to flower pieces and slurry stains. Simply reducing the slurry viscosity for printing is prone to high and low lines and excessive line width, which affects the battery conversion efficiency.
[0045] Therefore, after analysis and research, the inventor believes that in order to solve such problems, on the one hand, it is necessary to adjust the resin, increase the ink-passing property of the slurry, reduce the polar viscosity of the resin, and ensure the smoothness of printing and the line type after printing; on the other hand, it is necessary to appropriately increase the elastomer resin, increase the thixotropy of the slurry, maintain the line height of the slurry after printing, and obtain a high grid line aspect ratio. Based on the above concept, the present invention provides a low-temperature silver-coated copper slurry for heterojunction batteries, a preparation method and application thereof, and the slurry can be suitable for nickel screen printing with higher slurry requirements. In addition, the slurry is also suitable for other printing methods with lower slurry requirements, such as screen printing, narrow line width screens, and steel meshes.
[0046] The present invention provides a low-temperature silver-coated copper conductive silver paste suitable for nickel screen printing of a new process for metallization of heterojunction solar cells. The components of the formula include, by mass ratio: 10%-70% of spherical silver-coated copper powder, 15-80% of silver powder, 0.5-5% of nano silver powder, 1-6% of resin, 0.2-4% of auxiliary agent, and 0.5-3% of solvent; wherein the resin includes but is not limited to epoxy resin with an epoxy equivalent of 200-260 and rubber-toughened epoxy resin with a weight average molecular weight of 10000-20000. In the paste, the epoxy resin with an epoxy equivalent of 200-260 is a low-molecular-weight, low-polarity resin, which is used to provide ink passing properties and ensure the narrow line width printing of the nickel screen; and the rubber-toughened epoxy resin with a weight average molecular weight of 10000-20000 is a high-molecular-weight resin, which serves as a thixotropic agent to ensure the printing line type and high aspect ratio.
[0047] By adopting the above-mentioned slurry technology solution and combining it with nickel mesh narrow line width printing, the line width can be as low as 18 microns, which greatly reduces the silver consumption of a single piece, increases the light utilization rate, improves the conversion efficiency of the battery cell, and achieves the goal of reducing costs and increasing efficiency.
[0048] In this article, the range expressed by "a value to another value" is a summary expression method to avoid listing all the values in the range one by one in the specification. Therefore, the description of a specific numerical range covers any value in the numerical range and a smaller numerical range defined by any value in the numerical range, just as if the arbitrary value and the smaller numerical range were explicitly written in the specification.
[0049] Below in conjunction with the accompanying drawings and specific embodiments, the preferred embodiments of the present invention are described in detail so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more explicit definition of the protection scope of the present invention. It should be understood that these embodiments are only used to illustrate the present invention, and are not used to limit the protection scope of the present invention. In practical applications, improvements and adjustments made by those skilled in the art according to the present invention still belong to the protection scope of the present invention.
[0050] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0051] In the following examples, the epoxy resin with an epoxy equivalent of 246 is a modified hydrogenated bisphenol A epoxy resin (a type of hydrogenated bisphenol A epoxy resin), and the rubber-toughened epoxy resin with a weight-average molecular weight of 16,000 is a core-shell structured rubber-toughened epoxy resin.
[0052] Example 1
[0053] This embodiment provides a low-temperature silver-coated copper paste for heterojunction batteries suitable for nickel screen printing and a preparation method thereof.
[0054] In parts by weight, the conductive silver paste comprises:
[0055] Spherical silver-coated copper powder 70% (D50 = 5 μm, tap density = 0.3 g / cm 3 , specific surface area 0.92m 2 / g), submicron ball powder 20% (D50 = 0.4 μm, tap density = 4.2 g / cm 3 , specific surface area 1.54m 2 / g), nano silver powder 3% (average particle size <0.1μm, specific surface area 4.1m 2 / g);
[0056] 2% epoxy resin with epoxy equivalent weight of 246, 0.8% rubber toughened epoxy resin with weight average molecular weight of 16000, and 1.0% blocked isocyanate;
[0057] Boron trifluoride ethylamine complex 0.1%, 2-ethyl-4-methylimidazole 0.1%, epoxy-terminated silane coupling agent 0.5%, diethylene glycol butyl ether acetate 2.5%.
[0058] The preparation method of the conductive silver paste comprises the following steps:
[0059] First, pour all the liquid components such as epoxy resin, additives, organic solvents into the reactor, control the temperature at 25°C, stir at 60r / min, and stir for 20 minutes;
[0060] Submicron ball powder, nano silver powder, and spherical silver-coated copper powder were added in sequence, the temperature was controlled at 25°C, the stirring speed was 60r / min, and the stirring was continued for 120 minutes to obtain a uniform slurry;
[0061] Then, the three-roll mill is used for grinding, and the grinding gap is adjusted from large to small to 120μm to 20μm;
[0062] Finally, the mixture was filtered through a 500-mesh screen to obtain a conductive silver paste with uniform dispersion and a viscosity of 100 to 200 Pa.s.
[0063] Example 2
[0064] This embodiment provides a low-temperature silver-coated copper paste for heterojunction batteries suitable for nickel screen printing and a preparation method thereof.
[0065] In parts by weight, the conductive silver paste comprises:
[0066] Spherical silver-coated copper powder 65% (D50 = 5 μm, tap density = 0.3 g / cm 3 , specific surface area 0.92m 2 / g), submicron ball powder 25% (D50 = 0.4 μm, tap density = 4.2 g / cm 3 , specific surface area 1.54m2 / g), the nano silver powder 3% (average particle size <0.1μm, specific surface area 4.1m 2 / g).
[0067] 2% epoxy resin with epoxy equivalent weight of 246, 0.8% rubber toughened epoxy resin with weight average molecular weight of 16000, and 1.0% blocked isocyanate;
[0068] Boron trifluoride ethylamine complex 0.1%, 2-ethyl-4-methylimidazole 0.1%, epoxy-terminated silane coupling agent 0.5%, diethylene glycol butyl ether acetate 2.5%.
[0069] The preparation method of the conductive silver paste comprises the following steps:
[0070] First, pour all the liquid components such as epoxy resin, additives, organic solvents into the reactor, control the temperature at 25°C, stir at 60r / min, and stir for 20 minutes;
[0071] Submicron ball powder, nano silver powder, and spherical silver-coated copper powder were added in sequence, the temperature was controlled at 25°C, the stirring speed was 60r / min, and the stirring was continued for 120 minutes to obtain a uniform slurry;
[0072] Then, the three-roll mill is used for grinding, and the grinding gap is adjusted from large to small to 120μm to 20μm;
[0073] Finally, the mixture was filtered through a 500-mesh screen to obtain a conductive silver paste with uniform dispersion and a viscosity of 100 to 200 Pa.s.
[0074] Example 3
[0075] This embodiment provides a low-temperature silver-coated copper paste for heterojunction batteries suitable for nickel screen printing and a preparation method thereof.
[0076] In parts by weight, the conductive silver paste comprises:
[0077] Spherical silver-coated copper powder 45% (D50 = 5 μm, tap density = 0.3 g / cm 3 , specific surface area 0.92m 2 / g), submicron ball powder 45% (D50 = 0.4 μm, tap density = 4.2 g / cm 3 , specific surface area 1.54m2 / g), nano silver powder 3% (average particle size <0.1μm, specific surface area 4.1m 2 / g);
[0078] 2% epoxy resin with epoxy equivalent weight of 246, 0.8% rubber toughened epoxy resin with weight average molecular weight of 16000, and 1.0% blocked isocyanate;
[0079] Boron trifluoride ethylamine complex 0.1%, 2-ethyl-4-methylimidazole 0.1%, epoxy-terminated silane coupling agent 0.5%, diethylene glycol butyl ether acetate 2.5%.
[0080] The preparation method of the conductive silver paste comprises the following steps:
[0081] First, pour all the liquid components such as epoxy resin, additives, organic solvents, etc. into the reactor, control the temperature at 25°C, stir at 60r / min, and stir for 20 minutes.
[0082] Submicron ball powder, nano silver powder and spherical silver-coated copper powder were added in sequence, the temperature was controlled at 25°C, the stirring speed was 60 r / min, and the mixture was stirred for 120 minutes to obtain a uniform slurry.
[0083] Then, grinding was performed using a three-roll mill, and the grinding gap was adjusted from large to small to 120 μm to 20 μm.
[0084] Finally, the mixture was filtered through a 500-mesh screen to obtain a conductive silver paste with uniform dispersion and a viscosity of 100 to 200 Pa.s.
[0085] Example 4
[0086] This embodiment provides a low-temperature silver-coated copper paste for heterojunction batteries suitable for nickel screen printing and a preparation method thereof.
[0087] In parts by weight, the conductive silver paste comprises:
[0088] Spherical silver-coated copper powder 45% (D50 = 5 μm, tap density = 0.3 g / cm 3 , specific surface area 0.92m 2 / g), submicron ball powder 25% (D50 = 0.4 μm, tap density = 4.2 g / cm 3 , specific surface area 1.54m2 / g?), submicron flake powder 20% (D50 = 0.4μm, tap density = 4.0g / cm 3 , specific surface area = 0.55m 2 / g) Nano silver powder 3% (average particle size <0.1μm, specific surface area 4.1m 2 / g);
[0089] 2% epoxy resin with epoxy equivalent weight of 246, 0.8% rubber toughened epoxy resin with weight average molecular weight of 16000, and 1.0% blocked isocyanate;
[0090] Boron trifluoride ethylamine complex 0.1%, 2-ethyl-4-methylimidazole 0.1%, epoxy-terminated silane coupling agent 0.5%, diethylene glycol butyl ether acetate 2.5%.
[0091] The preparation method of the conductive silver paste comprises the following steps:
[0092] First, pour all the liquid components such as epoxy resin, additives, organic solvents, etc. into the reactor, control the temperature at 25°C, stir at 60r / min, and stir for 20 minutes.
[0093] Submicron ball powder, submicron flake powder, nano silver powder and spherical silver-coated copper powder were added in sequence, the temperature was controlled at 25°C, the stirring speed was 60r / min, and the mixture was stirred for 120 minutes to obtain a uniform slurry.
[0094] Then, grinding was performed using a three-roll mill, and the grinding gap was adjusted from large to small to 120 μm to 20 μm.
[0095] Finally, the mixture was filtered through a 500-mesh screen to obtain a conductive silver paste with uniform dispersion and a viscosity of 100 to 200 Pa.s.
[0096] Example 5
[0097] This embodiment provides a low-temperature silver-coated copper paste for heterojunction batteries suitable for nickel screen printing and a preparation method thereof.
[0098] In parts by weight, the conductive silver paste comprises:
[0099] Spherical silver-coated copper powder 45% (D50 = 5 μm, tap density = 0.3 g / cm 3 , specific surface area 0.92m 2 / g), submicron ball powder 25% (D50 = 0.4 μm, tap density = 4.2 g / cm 3 , specific surface area 1.54m2 / g), submicron flake powder 20% (D50 = 0.4μm, tap density = 4.0g / cm 3 , specific surface area 0.55m 2 / g) Nano silver powder 3% (average particle size <0.1μm, specific surface area 4.1m 2 / g);
[0100] 1.5% epoxy resin with epoxy equivalent weight of 246, 1.3% rubber toughened epoxy resin with weight average molecular weight of 16000, and 1.0% blocked isocyanate;
[0101] Boron trifluoride ethylamine complex 0.1%, 2-ethyl-4-methylimidazole 0.1%, epoxy-terminated silane coupling agent 0.5%, diethylene glycol butyl ether acetate 2.5%.
[0102] The preparation method of the conductive silver paste comprises the following steps:
[0103] First, pour all the liquid components such as epoxy resin, additives, organic solvents, etc. into the reactor, control the temperature at 25°C, stir at 60r / min, and stir for 20 minutes.
[0104] Submicron ball powder, submicron flake powder, nano silver powder and spherical silver-coated copper powder were added in sequence, the temperature was controlled at 25°C, the stirring speed was 60r / min, and the mixture was stirred for 120 minutes to obtain a uniform slurry.
[0105] Then, grinding was performed using a three-roll mill, and the grinding gap was adjusted from large to small to 120 μm to 20 μm.
[0106] Finally, the mixture was filtered through a 500-mesh screen to obtain a conductive silver paste with uniform dispersion and a viscosity of 100 to 200 Pa.s.
[0107] Example 6
[0108] This embodiment provides a low-temperature silver-coated copper paste for heterojunction batteries suitable for nickel screen printing and a preparation method thereof.
[0109] In parts by weight, the conductive silver paste comprises:
[0110] Spherical silver-coated copper powder 45% (D50 = 5 μm, tap density = 0.3 g / cm 3 , specific surface area 0.92m 2 / g), submicron ball powder 25% (D50 = 0.4 μm, tap density = 4.2 g / cm 3 , specific surface area 1.54m2 / g), submicron flake powder 20% (D50 = 0.4μm, tap density = 4.0g / cm 3 , specific surface area 0.55m 2 / g) Nano silver powder 3% (average particle size <0.1μm, specific surface area 4.1m 2 / g);
[0111] 1% epoxy resin with epoxy equivalent weight of 246, 1.8% rubber toughened epoxy resin with weight average molecular weight of 16000, and 1.0% blocked isocyanate;
[0112] Boron trifluoride ethylamine complex 0.1%, 2-ethyl-4-methylimidazole 0.1%, epoxy-terminated silane coupling agent 0.5%, diethylene glycol butyl ether acetate 2.5%.
[0113] The preparation method of the conductive silver-coated copper slurry comprises the following steps:
[0114] First, pour all the liquid components such as epoxy resin, additives, organic solvents, etc. into the reactor, control the temperature at 25°C, stir at 60r / min, and stir for 20 minutes.
[0115] Submicron ball powder, submicron flake powder, nano silver powder and spherical silver-coated copper powder were added in sequence, the temperature was controlled at 25°C, the stirring speed was 60r / min, and the mixture was stirred for 120 minutes to obtain a uniform slurry.
[0116] Then, grinding was performed using a three-roll mill, and the grinding gap was adjusted from large to small to 120 μm to 20 μm.
[0117] Finally, the mixture was filtered through a 500-mesh screen to obtain a conductive silver paste with uniform dispersion and a viscosity of 100 to 200 Pa.s.
[0118] Example 7
[0119] This embodiment provides a low-temperature silver-coated copper paste for heterojunction batteries suitable for nickel screen printing and a preparation method thereof.
[0120] In parts by weight, the conductive silver paste comprises:
[0121] Spherical silver-coated copper powder 45% (D50 = 5 μm, tap density = 0.3 g / cm 3 , specific surface area 0.92m 2 / g), submicron ball powder 25% (D50 = 0.4 μm, tap density = 4.2 g / cm 3 , specific surface area 1.54m2 / g), submicron flake powder 20% (D50 = 0.4μm, tap density = 4.0g / cm 3 , specific surface area 0.55m 2 / g) Nano silver powder 3% (average particle size <0.1μm, specific surface area 4.1m 2 / g);
[0122] 1% epoxy resin with epoxy equivalent of 201, 1.8% rubber toughened epoxy resin with weight average molecular weight of 20000, and 1.0% blocked isocyanate;
[0123] Boron trifluoride ethylamine complex 0.1%, 2-ethyl-4-methylimidazole 0.1%, epoxy-terminated silane coupling agent 0.5%, diethylene glycol butyl ether acetate 2.5%.
[0124] The preparation method of the conductive silver-coated copper slurry comprises the following steps:
[0125] First, pour all the liquid components such as epoxy resin, additives, organic solvents, etc. into the reactor, control the temperature at 25°C, stir at 60r / min, and stir for 20 minutes.
[0126] Submicron ball powder, submicron flake powder, nano silver powder and spherical silver-coated copper powder were added in sequence, the temperature was controlled at 25°C, the stirring speed was 60r / min, and the mixture was stirred for 120 minutes to obtain a uniform slurry.
[0127] Then, grinding was performed using a three-roll mill, and the grinding gap was adjusted from large to small to 120 μm to 20 μm.
[0128] Finally, the mixture was filtered through a 500-mesh screen to obtain a conductive silver paste with uniform dispersion and a viscosity of 100 to 200 Pa.s.
[0129] Example 8
[0130] This embodiment provides a low-temperature silver-coated copper paste for heterojunction batteries suitable for nickel screen printing and a preparation method thereof.
[0131] In parts by weight, the conductive silver paste comprises:
[0132] Spherical silver-coated copper powder 45% (D50 = 5 μm, tap density = 0.3 g / cm 3 , specific surface area 0.92m 2 / g), submicron ball powder 25% (D50 = 0.4 μm, tap density = 4.2 g / cm 3 , specific surface area 1.54m2 / g), submicron flake powder 20% (D50 = 0.4μm, tap density = 4.0g / cm 3 , specific surface area 0.55m 2 / g) Nano silver powder 3% (average particle size <0.1μm, specific surface area 4.1m 2 / g);
[0133] 1% epoxy resin with epoxy equivalent weight of 260, 1.8% rubber toughened epoxy resin with weight average molecular weight of 11000, and 1.0% blocked isocyanate;
[0134] Boron trifluoride ethylamine complex 0.1%, 2-ethyl-4-methylimidazole 0.1%, epoxy-terminated silane coupling agent 0.5%, diethylene glycol butyl ether acetate 2.5%.
[0135] The preparation method of the conductive silver-coated copper slurry comprises the following steps:
[0136] First, pour all the liquid components such as epoxy resin, additives, organic solvents, etc. into the reactor, control the temperature at 25°C, stir at 60r / min, and stir for 20 minutes.
[0137] Submicron ball powder, submicron flake powder, nano silver powder and spherical silver-coated copper powder were added in sequence, the temperature was controlled at 25°C, the stirring speed was 60r / min, and the mixture was stirred for 120 minutes to obtain a uniform slurry.
[0138] Then, grinding was performed using a three-roll mill, and the grinding gap was adjusted from large to small to 120 μm to 20 μm.
[0139] Finally, the mixture was filtered through a 500-mesh screen to obtain a conductive silver paste with uniform dispersion and a viscosity of 100 to 200 Pa.s.
[0140] Comparative Example 1
[0141] Take the common silver-clad copper paste suitable for screen printing on the market, with a total silver content of 30%, which comes from the applicant's own conventional screen paste, product model T2F.
[0142] The slurries of Examples 1-6 and Comparative Example 1 were printed on 210 heterojunction silicon wafers using a printer, screen (nickel screen) and printing parameters consistent with each other, and the obtained cells were subjected to the following performance tests:
[0143] Including wet weight, line shape, aspect ratio, photoelectric conversion efficiency, 3D image after printing, etc.
[0144] The test results are shown in Table 1 below.
[0145] Table 1
[0146]
[0147] By comparing the test results of Examples 1, 2, and 3, it can be seen that as the silver content increases, the wet weight of the slurry increases, the line height increases, and the photoelectric conversion efficiency increases.
[0148] By comparing the test results of Examples 4, 5, and 6, it can be seen that as the ratio of epoxy resin to rubber-toughened epoxy resin is adjusted, different performances are observed in the photoelectric conversion efficiency; as the ratio of rubber-toughened epoxy resin increases, the photoelectric conversion efficiency first increases and then decreases; as the content of high molecular weight resin increases, the wet weight decreases.
[0149] Comparing Example 1 with Comparative Example 1, for the same 30% silver-containing slurry, the low-temperature silver-coated copper slurry for heterojunction solar cells provided by the present invention has better photoelectric conversion efficiency.
[0150] Figure 1-7 The 3D image detection results of Comparative Example 1 and Examples 1-6 are shown.
[0151] in,
[0152] Figure 1 In the comparative example 1 shown, the printing line is uneven and the burrs are serious;
[0153] The printing lines of Examples 3-4 with the same silver-containing slurry under the formulation of the present invention are smooth, with high line height, narrow line width, and high photoelectric conversion efficiency.
[0154] In addition, it can be seen from the comparison of Examples 1-3 that the higher the silver content, the higher the wet weight and the relatively smoother the line shape.
[0155] However, it can be seen from the comparison of Examples 4-6 that as the content of the rubber toughened epoxy resin increases, especially when the content ratio of the epoxy resin to the rubber toughened epoxy resin is that of Examples 5 and 6, the printed line type tends to deteriorate. Therefore, the content ratio of the rubber toughened epoxy resin needs to be controlled. Usually, the mass ratio of the epoxy resin with an epoxy equivalent of 200-260 and the rubber toughened epoxy resin with a weight average molecular weight of 10,000-20,000 is controlled to be 10:90-90:10. More preferably, the mass ratio of the rubber toughened epoxy resin with a weight average molecular weight of 10,000-20,000 in the resin can be controlled to be no more than 50%.
[0156] Comparative Examples 6-8 show that better aspect ratios can be obtained by controlling the epoxy equivalent of the resin within the range of 200-260 and the molecular weight of the rubber toughened epoxy resin within the range of 10,000-20,000.
[0157] Under the guidance of the present invention and the above-mentioned embodiments, it is easy for those skilled in the art to foresee that each raw material or its equivalent substitute, each processing method or its equivalent substitute listed or exemplified in the present invention can realize the present invention, and the upper and lower limit values and interval values of the parameters of each raw material and processing method can realize the present invention, and the embodiments are not listed one by one here.
[0158] The above description is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiment. Any equivalent modifications or changes made by ordinary technicians in this field based on the contents disclosed by the present invention should be included in the protection scope recorded in the claims.
Claims
1. A low-temperature silver-coated copper paste for heterojunction batteries, which can be used for nickel screen printing, characterized in that: The invention comprises the following components by mass ratio: 10%-70% of spherical silver-coated copper powder, 15-80% of submicron silver powder, 0.5-5% of nano silver powder, 1-6% of resin, 0.2-4% of auxiliary agent and 0.5-3% of solvent, wherein the resin comprises epoxy resin with epoxy equivalent of 200-260 and rubber toughened epoxy resin with weight average molecular weight of 10000-20000.
2. The low-temperature silver-coated copper slurry for heterojunction batteries according to claim 1, characterized in that: The rubber toughened epoxy resin is a kind of epoxy resin derivative, selected from one or a combination of functionalized liquid rubber toughened epoxy, composite β-cyclodextrin / terminated carboxyl liquid nitrile rubber co-toughened epoxy resin, and core-shell structure rubber toughened epoxy resin; the mass ratio of the epoxy resin with an epoxy equivalent of 200-260 and the rubber toughened epoxy resin with a weight average molecular weight of 10000-20000 is 10:90-90:
10.
3. The low-temperature silver-coated copper slurry for heterojunction batteries according to claim 1, characterized in that: The specific surface area of the spherical silver-coated copper powder is 0.1-0.6m 2 / g, D50 is 2.5-6 microns, and tap density is 4.5-5.5g / m 3 The spherical silver-coated copper powder includes one powder or a combination of multiple powders, wherein the combination of multiple powders is a combination of powders with different specific surface areas, D50 and tap density. The submicron silver powder includes one or more powders of submicron ball powder and submicron flake powder. The average particle size of the nano silver powder is less than 0.1 μm, and the specific surface area is 2 to 5.5 m 2 / g.
4. The low-temperature silver-coated copper slurry for heterojunction batteries according to claim 3, characterized in that: The particle size distribution of the submicron ball powder is D10≤0.2μm, D50≤0.6μm, D100≤1.5μm, and the tap density is 4.0-5.1g / cm 3 , specific surface area 0.7~1.3m 2 / g; the particle size distribution of the submicron flake powder is D10≤1.2μm, D50≤5μm, D100≤8μm, and the tap density is 5.1~6.2g / cm 3 , specific surface area 0.5~0.6m 2 / g.
5. The low-temperature silver-coated copper slurry for heterojunction battery according to claim 1, characterized in that: The resin comprises a mixture of an epoxy resin with an epoxy equivalent of 200-260, a rubber toughened epoxy resin with a weight average molecular weight of 10000-20000, and a curing agent; the curing agent is selected from one or more of amine compounds, imidazole compounds, acid anhydride compounds, isocyanate compounds, and mercapto compounds, or the curing agent is a latent curing agent; wherein the amine compound is one or more of dicyandiamide, boron trifluoride ethylamine complex, and boron trichloride ethylamine complex.
6. The low-temperature silver-coated copper slurry for heterojunction batteries according to claim 1 or 5, characterized in that: The epoxy resin with an epoxy equivalent of 200-260 is one or more of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol F epoxy resin, acrylic modified epoxy resin, silicone modified epoxy resin, and polyurethane modified epoxy resin.
7. The low-temperature silver-coated copper slurry for heterojunction batteries according to claim 1, characterized in that: The auxiliary agent includes one or more of a thixotropic agent, a leveling agent, a dispersant, a coupling agent, and an antioxidant; wherein the thixotropic agent is selected from one or more of fumed silica, organic bentonite, hydrogenated castor oil, polyamide wax, and oleic acid amide; the leveling agent is selected from one or more of acrylic acid, modified polysiloxane, and fluorocarbon compounds; the dispersant is selected from one or more of sulfonates, ammonium salts, carboxylates, polyesters, and polyurethanes; the coupling agent is selected from one or more of aminosilane coupling agents, epoxy-terminated silane coupling agents, titanate coupling agents, and aluminate coupling agents; the antioxidant is selected from one or more of metal ion chelating agents, citric acid, EDTA, and phosphoric acid derivatives.
8. The low-temperature silver-coated copper slurry for heterojunction batteries according to claim 1, characterized in that: The solvent is selected from one or more of diethylene glycol butyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether acetate, ethyl acetate, butyl acetate, naphtha, propylene glycol methyl ether acetate, dimethyl succinate, dimethyl glutarate, dimethyl adipate, tributyl citrate, dibutyl phthalate, butyl benzyl phthalate, butyl stearate, oleic acid, butyl oleate, terpineol, and tributyl phosphate.
9. A method for preparing the low-temperature silver-coated copper slurry for heterojunction batteries according to any one of claims 1 to 8, characterized in that: The steps include: First, pour the resin, the auxiliary agent, the solvent and other components into a reaction kettle and stir and mix; Then, the submicron silver powder, the nano silver powder, and the spherical silver-coated copper powder are added in sequence, and stirred to obtain a uniform slurry; Then, the three-roll mill is used for grinding, and the grinding gap is adjusted from large to small to 120μm to 20μm; Finally, the conductive silver paste is filtered through a sieve to obtain a uniformly dispersed conductive silver paste with a viscosity of 100 to 200 Pa.s.
10. Use of the low-temperature silver-coated copper paste for heterojunction batteries according to any one of claims 1 to 8 in preparing heterojunction batteries by nickel screen printing.
Citation Information
Cited By
High-reliability conductive silver paste for heterojunction solar cell and preparation method of high-reliability conductive silver paste
CN117954145A
High-reliability conductive silver paste for heterojunction solar cells and preparation method thereof
CN117954145B
Modified silver-coated copper powder, electronic paste applying same and preparation method of modified silver-coated copper powder
CN120533091A
Silver-coated copper powder for narrow line width printing with steel mesh and preparation method thereof
CN122517606A